2023
DOI: 10.1080/14756366.2023.2251712
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis, biological evaluation and molecular docking study of novel pleuromutilin derivatives containing substituted benzoxazole as antibacterial agents

Jie Ren,
Qi-Wen Zhang,
Xian-Jin He
et al.

Abstract: A series of pleuromutilin analogs containing substituted benzoxazole were designed, synthesised, and assessed for their antibacterial activity both in vivo and in vitro . The MIC of the synthesised derivatives was initially assessed using the broth dilution method against four strains of Staphylococcus aureus (MRSA ATCC 43300, S. aureus ATCC 29213, clinical isolation of S. aureus AD3 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…In our previous studies, it was found that the introduction of different biologically active heterocyclic and aromatic rings into the C14 side chain of the pleuromutilin could enhance the antimicrobial activity, including triazole, oxadiazole, benzimidazoles, and others. The introduction of different substituents into the side chain may affect the mode of action of the side chain with PTC and improve the activity of pleuromutilin derivatives .…”
Section: Results and Discussionmentioning
confidence: 99%
“…In our previous studies, it was found that the introduction of different biologically active heterocyclic and aromatic rings into the C14 side chain of the pleuromutilin could enhance the antimicrobial activity, including triazole, oxadiazole, benzimidazoles, and others. The introduction of different substituents into the side chain may affect the mode of action of the side chain with PTC and improve the activity of pleuromutilin derivatives .…”
Section: Results and Discussionmentioning
confidence: 99%